2023
DOI: 10.1590/0103-6440202305539
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behavior of different designs of hybrid abutment-restoration on the posterior crown: a finite element analysis

Adna Alves Rocha,
Marco Aurélio de Carvalho,
Dimorvan Bordin
et al.

Abstract: This study aimed to evaluate the influence of material and crown design on the biomechanical behavior of implant-supported crowns with hybrid abutment (HA) through three-dimensional (3D) finite element analysis. The study factors were the type of material used as the mesostructure or crown (zirconia, lithium disilicate, and hybrid ceramic) and the crown design cemented to the titanium base (mesostructure cemented to the titanium base and a crown cemented on it (HaC); hybrid crown-abutment, the abutment and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This was because the loading methods used in this study were area loading, and the stresses were concentrated in the loading area and then transferred to other areas. The study by Rocha et al also found that stresses will be concentrated in the loading area of the restoration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was because the loading methods used in this study were area loading, and the stresses were concentrated in the loading area and then transferred to other areas. The study by Rocha et al also found that stresses will be concentrated in the loading area of the restoration [ 35 ].…”
Section: Discussionmentioning
confidence: 99%